Dietary L-proline supplementation ameliorates autism-like behaviors and modulates gut microbiota in the valproic acid-induced mouse model of autism spectrum disorder - Jingjing Fang; Ruixuan Geng; Seong-Gook Kang; Kunlun Huang; Tao Tong (Food Science and Human Wellness)
The effective intervention strategy for autism spectrum disorder (ASD) are currently limited. Herein, we attempted to evaluate the potential of L-proline (Pro), a multifunctional amino acid, in ameliorating autism-like behaviors and clarify the molecular mechanisms involved by using the typical valproic acid (VPA)-induced mouse model of ASD. Pro significantly attenuates repetitive behaviors and social dysfunction in ASD mice. The correlation analysis revealed that the beneficial effects of Pro on autism-like behaviors are related to the modulation of gut microbiota structure and composition. The histological analysis revealed that Pro could reverse the decrease of Nissl-positive cells in the prefrontal cortex (PFC) induced by VPA exposure. RNA sequencing demonstrated that Pro can also alter the PFC transcriptomic profile distinguished by the regulation of genes involved in Parkinson disease, neuroactive ligand-receptor interaction, oxidative phosphorylation, and mitogen activated protein kinase signaling pathway. Overall, dietary Pro supplementation may be a promising intervention strategy for ASD.